Case Report: Successful delivery following chemotherapy in a pregnant patient with metastatic SMARCB1-deficient renal medullary carcinoma - Kontoyiannis, Panayiotis D.; Kuykendal, Adam; Tang, Chad; Cheng, Jessica P.; Chan, Beei; Thomas, Susan S.; Rao, Priya; Lim, Bora; Msaouel, Pavlos (Frontiers in Oncology, 2025)
SMARCB1-deficient renal medullary carcinoma (RMC) is a rare and aggressive kidney cancer defined by the loss of SMARCB1 tumor suppressor and primarily affecting adolescents and young adults with sickle hemoglobinopathies. Approximately 7% of RMC cases, known as renal cell carcinoma unclassified with medullary phenotype (RCCU-MP), lack sickle hemoglobinopathy. RMC does not respond to immune checkpoint inhibitors and antiangiogenic tyrosine kinase inhibitors, with chemotherapy being the main treatment. Here we present the first documented case of RMC diagnosed during pregnancy. A 24-year-old woman presented with right-sided back pain, leading to the discovery of a 6-cm right renal mass. Pathology confirmed RCCU-MP with SMARCB1 loss. With the woman at 16 weeks into pregnancy, imaging revealed metastatic retroperitoneal lymphadenopathy and lung nodules. A chemotherapy regimen of doxorubicin and cyclophosphamide, followed by weekly paclitaxel, was selected for safety in pregnancy. This approach yielded significant tumor shrinkage and alleviated the symptoms, allowing for the safe, preterm delivery of a healthy baby at 33 weeks. Following delivery, the patient received combination chemotherapy and definitive radiation therapy, achieving disease control. At 2 years post-diagnosis, she remains alive, exceeding the median survival for RCCU-MP. This case demonstrates that established chemotherapeutic regimens used in pregnant patients with other cancers can be successfully applied to manage RMC during pregnancy. Our findings underscore the importance of early, aggressive treatment and suggest that a coordinated approach can achieve favorable outcomes for both the mother and the fetus.